2009
DOI: 10.1007/s00240-009-0243-z
|View full text |Cite|
|
Sign up to set email alerts
|

Preventive effects of COX-2 inhibitor, celecoxib on renal tubular injury induced by shock wave lithotriptor

Abstract: Our study was designed to investigate the protective effect of the COX-2 inhibitor, celecoxib, on renal tubules against shock wave lithotripsy (SWL). Sprague-Dawley rats were randomly divided into three groups: sham, control, and COX-2 groups. The control group was administrated normal saline. The COX-2 group was administered celecoxib (10 mg/kg). After administration for 1 week, the control and COX-2 groups received 1,000 shock waves. Before and after SWL, 24-h urine was collected. CCr was measured to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Kaurenoic acid is a diterpene with potent anti-inflammatory activity by the inhibition of the inducible nitric oxide synthase (iNOS) and ciclooxigenase-2 (COX-2) expression [28, 29]. COX-2 inhibitors such celecoxib have protective effects against transient renal dysfunction that occurs due to the shock waves in the shock waves lithotripsy treatment [30]. Additionally, it has been demonstrated that kaurenoic acid produces a vasorelaxation by inhibition of the Ca 2+ influx [31].…”
Section: Discussionmentioning
confidence: 99%
“…Kaurenoic acid is a diterpene with potent anti-inflammatory activity by the inhibition of the inducible nitric oxide synthase (iNOS) and ciclooxigenase-2 (COX-2) expression [28, 29]. COX-2 inhibitors such celecoxib have protective effects against transient renal dysfunction that occurs due to the shock waves in the shock waves lithotripsy treatment [30]. Additionally, it has been demonstrated that kaurenoic acid produces a vasorelaxation by inhibition of the Ca 2+ influx [31].…”
Section: Discussionmentioning
confidence: 99%
“…Cyclooxygenase-2 (COX-2), the inducible isoform of COX, has only been found in a few organs, including the kidneys [17]. Selective COX-2 inhibitors provide potent anti-inflammatory and analgesic effects without the side effects of gastric and renal toxicity and inhibition of platelet function [18].…”
Section: Introductionmentioning
confidence: 99%